A furostan saponin isolated from the rhizome of C. spectabilis (Costaceae) exerts cataract ameliorative effect in-vitro - Salisu Shehu; Umar Habib Danmalam; Najma Ilyas; Mohammed Nuhu Danjuma; Aliyu Muhammed Musa (Islamic Azad University, Shahrekord Branch, 2023)
Background & Aim: Extracts from plants, such as C. spectabilis (rhizome) traditionally used for the treatment of cataract may potentially contain anticataract lead compound(s). The current study aimed to isolate the constituent(s) of the extract of C. spectabilis and evaluate its anticataract effect. Experimental: The isolation of the constituent was achieved using silica gel, sephadex column chromatography and preparative thin layer chromatography of the n-butanol fraction of aqueous ethanol extract of the rhizome, followed by analysis using NMR spectroscopy. The anticataract effect was investigated using H2O2-induced cataract model. Lenses freshly obtained from rats were cultured in the presence or absence of hydrogen peroxide (0.5 mM), and or in the presence of H2O2 (0.5 mM) with any of the three concentrations of compound SL1 (0.5 mgmL-1, 0.25 mgmL-1, or 0.125 mgmL-1 ) over a period of 24 hrs. Lens opacity (index of cataract) was quantified by scoring and image analysis. The lens total protein, antioxidant bio-molecules (GSH, SOD) and lipid peroxidation (MDA level) were determined according to standard methods. Results: Chromatographic fractionation of the extract led to the isolation of a compound characterised as 3-O-α-L-rhamnopyranosyl (1→2)-α-O-β-D-glucopyranoside (25R)-furost-5-ene-3β, 22α, 26-triol-26-O- β-D-glucopyranoside based on its NMR data. The lenses treated with hydrogen peroxide (only) demonstrated significantly higher indices of opacity compared to the normal or compound treated. The groups treated with the compound (at 0.5 and 0.25 mgmL-1 concentrations) significantly (P≤ 0.001) exhibited lower score of opacity and grey image pixel intensity compared to the untreated group. Although the compound significantly (P≤0.05) prevented the depletion of lens total protein at all concentrations used, the loss of GSH, SOD and increase in MDA levels induced by H2O2 were not prevented significantly. Recommended applications/industries: The compound isolated can serve as a promising lead for the development of anticataract drug.